Job stress and job satisfaction of mainstream and special education teachers in Singapore - Chua, Emily Xing Ting (2017)
Being a teacher has been considered as one of the most stressful job in Singapore. Hence, understanding the stressors, level of stress and job satisfaction is important to minimise the turnover rate in teachers. There were a total of 50 mainstream and 33 special education (SPED) teachers participated in this study. These teachers completed a total of four questionnaires including a demographic questionnaire, two stress-related, and a job satisfaction questionnaire. SPSS software was used to analyse the obtained results. Means and standard deviation for the five stress factors and stress manifestations were calculated to determine the stressors and the types of response commonly displayed. T test was used to test the means difference and Pearson was used to measure the correlation between stress and satisfaction. Demographics factors (gender, years of teaching experience and age) were also included in the analysis. The results revealed that the two groups of teachers have a significant difference in their level of stress but not for job satisfaction. Mainstream teachers were more stress (M = 88.4) than SPED teachers (M = 79.7). Too much administrative work with too little time given was the most prominent stressor in both teachers. None of the demographic comparison between and within teachers was significant except SPED teachers with 6 to 10 years of teaching experience (M=94.4) have a significant higher stress than SPED teachers with less than 5 years of teaching experience (M=75.7). It was found that as stress level increases, satisfaction level will decrease and vice versa.